Physicochemical and adsorptive properties of biochar derived from municipal sludge: sulfamethoxazole adsorption and underlying mechanism - Qiu, Xiaojie; Zhao, Yingxin; Zhao, Cailian; Jin, Ruotong; Li, Chenxi; Mutabazi, Emmanuel (Frontiers in Environmental Science, 2023)
In this study, municipal sludge derived biochar (SBC) was successfully synthesized via one-pot pyrolysis method, and the yield of sludge biochar gradually decreased with the pyrolysis temperature increased from 300 ℃ to 800 ℃. The sludge biochar exhibited alkaline surface due to the gradual accumulation of ash and the formation of carbonate and organic anion during high temperature pyrolysis process. Moreover, the prepared samples were analyzed by different characterization techniques including BET, SEM and XPS. Adsorption experiments using the optimized biochar sample of SBC800 resulted in a 95% sulfamethoxazole (SMX) removal efficiency and the maximum adsorption capacity of 7033.4 mg/kg, which was 47.5 times higher than that of SBC300. The adsorption process of SBC800 for SMX is more in line with Freundlich and D-A isotherm model, the whole process is exothermic reaction. SBC800 could effectively remove SMX through pore filling effect, electrostatic attraction, hydrogen bonding, hydrophobic effect and π-π EDA interaction. Site energy distribution analysis showed that SMX preferentially occupied the high-energy adsorption site of SBC800, and then gradually diffused to the low-energy adsorption site. This study proposed a sustainable method for recycling municipal sludge for organic pollutant removal.